DEVELOPMENT OF GYRODACTYLUS NEONEPHROTUS MALMBERGI SINGH AND AGRAWAL, 1994 IN RELATION TO HOST BODY LENGTH - SINGH, H. S.; AGRAWAL, SHILPI; SHARMA, BINDU (UTTAR PRADESH JOURNAL OF ZOOLOGY, 1995)
Present paper deals with developmental stages of Gyrodactylus sp., on the host, Heteropneustes fossilis (Bloch), in relation to the host body length.